Occurrence of pesticides in polished rice samples from Tanjung Karang and Sekinchan and the health risk among consumers - Ho, Yu Bin; Zabaruddin, Nurul Asyikin; Tan, Chung Keat (UPM Press, 2023)
Introduction: One of the key staple foods in many different countries, including Malaysia, is rice (Oryzae sativa L.). Pesticides are used to reduce weed growth and safeguard crops from insect attacks in order to boost paddy output. Objective: This research quantifies the concentration of pymetrozine, chlorantraniliprole, and difenoconazole, along with any potential health risks to consumers. Methods: Samples of polished rice from three rice milling factories in Tanjung Karang and Sekinchan were extracted using the QuEChERS (Quick Easy Cheap Effective Rugged Safe) technique. The amount of pesticide residue in polished rice was then measured using ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). A health risk assessment was conducted utilizing the Hazard Quotient (HQ) and Lifetime Cancer Risk (LCR) to estimate the non-carcinogenic and carcinogenic health risks. Results: The mean concentration of pesticides in polished rice ranged from less than the detection limit (difenoconazole) to 1.122 µg/kg (pymetrozine). No rice samples above the Maximum Residue Limit (MRL) specified in the Food Act 1983 as implemented by Malaysia’s Food Regulations 1985. Pymetrozine, chlorantraniliprole, and difenoconazole in rice had respective MRLs of 50 µg/kg, 2000 µg/kg, and 100 µg/kg. For all age groups, no significant non-carcinogenic health risk was associated with consuming polished rice from the study area, where the HQ and Hazard Index (HI) were less than one. When LCR values were less than 10-6, carcinogenic health risks of consuming polished rice from the study area were at a clearly acceptable risk level. Conclusion: As no sample exceeded the MRL, the findings indicated that all rice samples collected from Tanjung Karang and Sekinchan were safe for consumption.